Comparative Insilico Analysis of RuBisCo Proteins of Green, Red, and Brown Seaweeds - M, Thangaraj (JSMARTech: Journal of Smart Bioprospecting and Technology, 2025)
In this study, Ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO) was selected from three seaweeds such as Ulva lactuca (Green algae), Gracilaria edulis (Red algae) and Sargassum fusiforme (Brown algae) to predict the physicochemical characters, secondary and 3-D structure properties using appropriate bioinformatics tools. The result showed that, the least percentage amino acid was Cys (0.8%) occurred in G. edulis and the highest percentage of amino acid was Gly (10%) in U. lactuca. Three amino acids such as Lys, Ser and Trp were more or less in same percentage in all the three seaweeds. The maximum molecular weight (MW) was predicted as 54.11 KDa in G. edulis. As per the theoretical pI, the proteins were acidic in nature in all the three seaweeds and the values ranged from 5.62 to 5.98. The instability index (II) values for this protein was 27.05, 29.11, 37.38 in S. fusiforme, G. edulis and U. lactuca respectively which shows the protein was stable.  GRAVY value was found to be -0.110, -0.127, and -0.263 which indicated that the protein was hydrophilic and water-soluble.  The secondary structure of this protein primarily composed of α-helixes and β-sheets, revealing the stable structure. The modeling of the 3-D structure of this protein was performed by Swiss model and the model was validated by PROCHECK and QMEAN. The results of this study may provide valuable insights into fundamental characteristics of RuBisCO proteins in different seaweeds.